Neoadjuvant Programmed Cell Death 1 (PD-1) Inhibitor Treatment in Patients With Hepatocellular Carcinoma Before Liver Transplant: A Cohort Study and Literature Review - Qiao, Zi-yun; Zhang, Zi-jie; Lv, Zi-cheng; Tong, Huan; Xi, Zhi-feng; Wu, Hao-xiang; Chen, Xiao-song; Xia, Lei; Feng, Hao; Zhang, Jian-jun; Xia, Qiang (Frontiers in Immunology, 2021)
Programmed cell death 1 (PD-1) blockade is considered contraindicated in liver transplant (LT) recipients due to potentially lethal consequences of graft rejection and loss. Though post-transplant PD-1 blockade had already been reported, pre-transplant use of PD-1 blockade has not been thoroughly investigated. This study explores the safety and efficacy of neoadjuvant PD-1 blockade in patients with hepatocellular carcinoma (HCC) after registration on the waiting list. Seven transplant recipients who underwent neoadjuvant PD-1 blockade combined with lenvatinib and subsequent LT were evaluated. The objective response rate (ORR) and disease control rate (DCR) was 71% and 85% according to the mRECIST criteria. Additionally, a literature review contained 29 patients were conducted to summarize the PD-1 blockade in LT for HCC. Twenty-two LT recipients used PD-1 inhibitors for recurrent HCC. 9.1% (2/22) and 4.5% (1/22) recipients achieved complete remission (CR) and partial remission (PR), respectively; 40.9% (9/22) recipients had progressive disease (PD). Allograft rejection occurred in 45% of patients. In total, seven patients from our center and three from the literature used pretransplant anti-PD-1 antibodies, eight patients (80%) had a PR, and the disease control rate was 100%. Biopsy-proven acute rejection (BPAR) incidence was 30% (3 in 10 patients), two patients died because of BPAR. This indicated that neoadjuvant PD-1-targeted immunotherapy plus tyrosine kinase inhibitors (TKI) exhibited promising efficacy with tolerable mortality in transplant recipients under close clinical monitoring.